Impact Of Sales Growth And Company Size Towards Financial Structure - Danna Solihin; Adisthy Shabrina Nurqamarani (ProBank, 2021)
The research examines impacts of sales growth and company size to financial structure. Research conducted at firms in mining industries which go public in Indonesia Stock Exchange. Data were analyzed using multiple regression analysis. The results of the research show that the sales growth and company size positively affect the firms’ financial structure in the mining sector listed on the Indonesia Stock Exchange. Sales growth variable has significant effect while company size has no significant effect to financial structure. Furthermore, during the last three years between 2013-2015, sales growth and the company size of mining sector companies continue to decline. This is due to the decline in world coal prices followed by slowing demand for coal and crude oil. Consequently, policy makers and managers of mining industries should consider sales growth and company size in arranging the company financial structure. They can use based on these findings, especially more attention on sales growth to manage that financial structure